Developing Teacher Professionality Through Education Supervision - Elpires Muhamad Niku; Maisyaroh Maisyaroh; Syamsul Hadi (International Research-Based Education Journal, 2020)
This article aims to describe developing professionalism of teachers through educational supervision. As related to the discussion isteacher professionalism includes understanding of the profession, understanding of professionalism, measurement of teacher professionalism, and the influence of teacher professionalism on learning outcomes. Andeducational supervision includes understanding of educational supervision, the objectives and functions of educational supervision, types of educational supervision, as well as the principles and approaches in educational supervision. The results of the discussion can show (a) develop teacher professionalism possessed ability which is the result of cognitive work to carry out tasks so that students obtain optimal learning outcomes, so that the creation of quality or quality education, and (b) through the supervision of education  coaching activities or activities carried out by a professional to assist teachers and other education personnel in improving teaching materials, methods and evaluations by continuously stimulating, coordinating and mentoring so that teachers become more professional in increasing the achievement of school goals